2022
DOI: 10.3389/fpsyg.2022.920594
|View full text |Cite
|
Sign up to set email alerts
|

Éclaircissement to Understand Consumers’ Decision-Making Psyche and Gender Effects, a Fuzzy Set Qualitative Comparative Analysis

Abstract: Consumers’ decision-making is complex and diverse in terms of gender. Different social, psychological, and economic factors mold the decision-making preferences of consumers. Most researchers used a variance-based approach to explain consumer decision-making that assumes symmetric relationship between variables. We have collected data from 468 smartwatch users and applied a fuzzy set qualitative comparative analysis (fsQCA) to explain and compare male and female consumers’ decision-making complexity. fsQCA ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 48 publications
3
34
0
Order By: Relevance
“…We have decided to study gender-specific paths to clarify the role of personality traits in online teaching/learning mode's satisfaction and adoption. Male and females differently perceive things and have different psych toward adopting a technology (Mustafa et al, 2022a) and contributing knowledge to online Q and A communities (Mustafa and Wen, 2022;Mustafa et al, 2022c). The same is found in the case of personality traits; gender differences in personality traits and the influence of personality traits are different for men and women (Narang et al, 2022).…”
Section: Gender Influencementioning
confidence: 93%
See 1 more Smart Citation
“…We have decided to study gender-specific paths to clarify the role of personality traits in online teaching/learning mode's satisfaction and adoption. Male and females differently perceive things and have different psych toward adopting a technology (Mustafa et al, 2022a) and contributing knowledge to online Q and A communities (Mustafa and Wen, 2022;Mustafa et al, 2022c). The same is found in the case of personality traits; gender differences in personality traits and the influence of personality traits are different for men and women (Narang et al, 2022).…”
Section: Gender Influencementioning
confidence: 93%
“…Satisfaction from technology leads to adoption and use of technology or product. Researchers have found that satisfaction from 5G services leads to their adoption in the future (Mustafa et al, 2022d), electronic gadgets (Mustafa et al, 2022a), electronic vehicle adoption (Mustafa et al, 2021), the effect of climate change and adoption techniques to minimize risk (Sohail et al, 2022b), green transportation adoption (Sohail et al, 2021). Furthermore, researchers have revealed that the level of satisfaction experienced by users will have a favorable and substantial influence on their desire to continue using academic library applications (Rafique et al, 2021).…”
Section: Satisfaction and Adoption Intentionmentioning
confidence: 99%
“…Ethics in basic research were taken into account when defining the research goals and collecting data from agricultural communities, and the research goal was clearly explained to agricultural communities (Resnik et al, 2015). Furthermore, agricultural communities were made aware that the information they provided would only be used for research and that they were not obligated to provide any answers (Bell et al, 2005;Rasool et al, 2017;Mustafa et al, 2022;Rehman et al, 2022;Ullah et al, 2022;Atchike et al, 2022). This instrument contained a brief introduction to the study's purpose, followed by a demographic questionnaire to determine the participants' ages, occupations, and other relevant information.…”
Section: Methodology Study Area and Datamentioning
confidence: 99%
“… Cao et al (2021) illustrate commitment as a ‘practical part of the social identity of online purchase. Wei et al (2016) emphasized the need for an empirical study of the impact of remuneration motivations on commitment and online purchase intentions in social media marketing ( Mustafa et al, 2022a ). We suggest that if retailers/brands in social media meet the remunerative needs of consumers, they can continue to build a commitment and even encourage the buying intentions of customers online.…”
Section: Literature Reviewmentioning
confidence: 99%